Successful Endoscopic Closure of Pyeloduodenal Fistula Using an Over-the-Scope Clip. Issue 11 (November 2019) - Duh, Erica; Clary, Meredith; Samarasena, Jason; Clayman, Ralph V.; Chang, Kenneth
Abstract : ABSTRACT: A 62-year-old woman underwent a series of urologic procedures for nephrolithiasis and was diagnosed with a pyeloduodenal fistula (PDF) on computed tomography urography. After the placement of a metallic ureteral stent and nephrostomy tube, an esophagogastroduodenoscopy was performed to evaluate for PDF resolution. Two areas of mucosal defects within the anterior duodenal sweep were closed using the over-the-scope clip system and hemostasis clips. We review the literature and discuss the etiologies, presentation, diagnosis, and treatment of PDF. This is the second documented case of endoscopic PDF closure using the over-the-scope clip system and the third case of endoscopically treated PDF.